Gum Arabic Ameliorates Impaired Coagulation and Cardiotoxicity Induced by Water-Pipe Smoke Exposure in Mice - Nemmar, Abderrahim; Al-Salam, Suhail; Beegam, Sumaya; Yuvaraju, Priya; Ali, Badreldin H. (Frontiers in Physiology, 2019)
Water-pipe smoking (WPS) is prevalent in the East and elsewhere. WPS exposure is known to induce thrombosis and cardiovascular toxicity involving inflammation and oxidative stress. Here, we have investigated the effect of Gum Arabic (GA), a prebiotic with anti-oxidant, anti-inflammatory and cytoprotective properties, on WPS exposure (30 min/day for 1 mo) on coagulation and cardiac homeostasis, and their possible underlying mechanisms in mice. Animals received either GA in drinking water (15%, w/v) or water only for the entire duration of study. GA significantly mitigated thrombosis in pial microvessels in vivo, platelet aggregation in vitro, and the shortening of prothrombin time induced by WPS exposure. The increase in plasma concentrations of fibrinogen, plasminogen activator inhibitor-1 and markers of lipid peroxidation, 8-isoprostane and malondialdehyde, induced by WPS were significantly reduced by GA administration. Moreover, WPS exposure induced a significant increase in systolic blood pressure and the concentrations of the pro-inflammatory cytokines tumor necrosis factor-α and interleukin 1β in heart homogenates. GA significantly alleviated these effects, and prevented the decrease of reduced glutathione, catalase and total nitric oxide levels in heart homogenates. Immunohistochemical analysis of the hearts showed that WPS exposure increased nuclear factor erythroid-derived 2-like 2 (Nrf2) expressions by cardiac myocytes and endothelial cells, and these effects were potentiated by the combination of GA and WPS. WPS also increased DNA damage and cleaved caspase 3, and GA administration prevented these effects. Our data, obtained in experimental murine model of WPS exposure, show that GA ameliorates WPS-induced coagulation and cardiovascular inflammation, oxidative stress, DNA damage and apoptosis, through a mechanism involving Nrf2 activation.